Scoring Scale to Assess the Body Condition of Draft Donkeys in North Cameroon - E. Vall; A. L. Ebangi; O. Abakar (Revue d’Elevage et de Médecine Vétérinaire des Pays Tropicaux, 2001)
Donkey traction began in North Cameroon in the 1970’s and is today used by 25,000 smallholders. The donkey work power is just about sufficient to perform at the smallholding level. To sustain donkeys’ work effort it is essential to keep them fed adequately, which is not nearly the case today. In this study the nutritional status of the draft donkey was characterized by a body condition scoring (BCS) scale. A BCS from 1-4 (emaciated, thin, average, good) was given to the back and flank of the donkey after considering by sight the pelvis, spinal column and side. The average of both scores were rounded up to the half point above to obtain the final score. The correlation of scores among various score givers was about 80%, which was a good indication of its reproducibility. A total of 41 males and 34 females were monitored. A BCS of 3 prevailed (50-70%) during the dry season. Thin animals (BCS of 2) rebuilt their food reserves in October-January, benefiting from seasonal and pathological changes. On the other hand, good animals (BCS of 4) lost weight at the first harsh occurrence of the dry season. All the animals but she-donkeys lost weight from January to June because feed resources became progressively scarce. A BCS of 2 was given in 10% of males at the beginning of the dry season and in 20% at the end of the dry season, whereas that score of 2 remained constant in 30-40% females all year round. Actions to improve the donkey nutritional status should be aimed primarily at females.